Intermediates in the intermolecular, asymmetric Heck arylation of dihydrofurans - Hii, K; Claridge, T; Brown, J (1997)
Double isomerization results in a Pd alkyl compound with unexpected structure, which is stable until -40, from the reaction of the Pd complex shown on the right with 2,3-dihydrofuran. The course of the asymmetric Heck reaction was followed by NMR spectroscopy. P(a)P(b) = (S)-BINAP.